Impact of Aspiration Pressure on Oocyte Quality and Retrieval Outcomes in FSH Pre-Stimulated Sahiwal Cows - Badugu, Abhay Kumar; K, Sai Gunaranjan; Veerabramaiah, K; Reddy L S S, Vara Prasad; Allu, Teja; Krishna N, Venkata; G, Sandeep Kumar (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Ovum pick-up (OPU) followed by in vitro embryo production (IVEP) is an efficient tool to accelerate genetic progress in cattle, particularly indigenous breeds that possess superior adaptability and disease resistance. The present study evaluated the effect of two vacuum pressures (40 vs. 50 mmHg) on oocyte recovery, quality and blastocyst rate in 16 Sahiwal donor cows that were hormonally pre-stimulated with follicle-stimulating hormone (FSH). Animals were randomly assigned to two groups (n=8 each) and subjected to OPU at either 40 mmHg or 50 mmHg. The mean number of cumulus-oocyte complexes (COCs) recovered per session was higher in the 50 mmHg group (26.13 ± 2.92) compared with the 40 mmHg group (20.63 ± 3.94). A significantly greater proportion of viable oocytes (Grades A+B+C) was recovered at 50 mmHg (74.16%) compared to 40 mmHg (71.51%), while the proportion of degenerated oocytes (Grades D+E) was lower (24.88% vs. 45.45%). Following in vitro maturation (IVM), an average 76.4±1.5% of recovered oocytes exhibited cumulus expansion. Of these, 62% of total oocytes (78.7±1.6% of matured) were successfully fertilized under in vitro fertilization (IVF) conditions. By Day 7 of culture, 34% of total oocytes and 43.3 ± 1.8% of matured oocytes developed into blastocysts, with a significantly higher mean blastocyst yield per OPU in the 50 mmHg group (8.5±0.9 vs 6.8±0.8). These findings demonstrate that aspiration at 50 mmHg not only enhances the yield and quality of oocytes but also improves there in vitro developmental competence up to the blastocyst stage. The results have practical implications for improving IVEP efficiency in elite Sahiwal cows and conserving valuable indigenous germplasm.